Essays in health economics - Nurminen, Mikko (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku, Turku School of Economics|, 2021)
This doctoral thesis studies efficiency in health care provision, with a dual focus on two themes. The first theme studies empirically how the introduction of health information technology affects access to prescription drugs, quality of prescribing and coordination between providers. The second theme studies empirically competition and mergers and acquisitions (M&As) in the private health care market. The thesis consists of an introductory chapter and four separate essays. The first essay considers how the introduction of electronic prescribing (e-prescribing), a technology that is designed to make prescribing and renewal of prescriptions easier and to improve patient monitoring, impacts access to and use of prescription drugs in the Finnish primary health care. We study a class of essential prescription drugs used in the treatment of mental health conditions and insomnia, but which are also highly addictive in long-term use. We find that e-prescribing increases the use of these prescription drugs in younger patients through the easier renewal of prescriptions. We do not find any improvement in health outcomes in this population, but find a significant increase in prescription drug abuse diagnoses and suicide attempts. The results imply that easier access without sufficient monitoring may facilitate the overuse of prescription drugs. The second essay studies how e-prescribing affects coordination between providers and quality of prescribing in terms of harmfully interacting prescriptions. We document a large discrepancy in the prevalence of interacting prescriptions with rural areas overrepresented. We find that e-prescribing decreases the probability of prescribing interacting prescriptions by 36 percent in rural municipalities, but not in urban municipalities. The decrease is largely explained by decreases in the probability in settings with different prescribers and unspecialized physicians. E-prescribing can enhance coordination among providers by improving information flow, especially when multiple physicians are involved and physicians are less experienced. The third essay studies the impacts of M&As on physician service markets in Finnish private health care. This essay considers how M&As affects competition between physicians through labor market outcomes, and how this translates to physician prices. We find that prices increase most for gynecologists, a physician group where switching costs and inertia are high. We find that local competition decreases among these physicians through job losses after M&As. This increases the market power of incumbent physicians in the acquired health care units. The essay shows that local competition has a meaningful impact on prices and that labor market outcomes can influence this competition. The final essay studies how M&As affect diagnostic service prices in the Finnish private health care sector. I study separately three different procedures: blood tests, X-rays, and MRIs. I find that M&As increase blood test prices significantly in the acquired health care units but do not meaningfully impact X-ray and MRI prices. Furthermore, I find that, in the same markets, the prices increase similarly in the acquiring firms’ other units, but not in the rivaling units. I proceed to estimate a patient demand model, which reveals that prices have little impact on the choice of the provider of blood tests. Instead, the referring physician has a large influence on the choice. Additionally, due to the small price coefficient, the change in consumer surplus from increased prices is negligible. Because of the patients’ low sensitivity to prices, firms may be able to increase their price-cost margins after M&As.